Foliar fertilization of nickel affects growth, yield component and micronutrient status of barley (Hordeum vulgare L.) grown on low nickel soil. Issue 10 (24th August 2018) - Kumar, Omkar; Singh, Satish Kumar; Latare, Ashish Maroatrao; Yadav, Shobha Nath
ABSTRACT: Foliar application of nickel (Ni) has higher use efficiencies and is preferred over soil application in view of its very low requirement. Pot experiments were conducted during winter season of 2012-2013 and repeated during 2013-2014.  Treatments consisted of twelve Ni levels applied as nickel sulphate (NiSO4.7H2 O) spray (T1 -Ni0%, T2 -Ni0.05%, T3 -Ni0.1%, T4 -Ni0.2%, T5 -Ni0.3%, T6 -Ni0.4%, T7 -Ni0.5%, T8 -Ni0.6%, T9 -Ni0.7%, T10 -Ni0.8%, T11 -Ni0.9%, and T12 -Ni1.0%, ) with recommended doses of fertilizers (RDF) applied in all pots. The result showed that growth and yield attributes viz. plant height, leaf greenness index, number of tillers, number of ears pot -1, number of grains ear -1, straw yield, grain yield and weight of 1000 grains of barley was the maximum with three foliar application of 0.2% of NiSO4.7H2 O (T4 -Ni0.2% ) at 20, 40, and 60 days after sowing (DAS) during both the years. The concentration of Fe, Mn and Zn in grain increased significantly up to T4 -Ni0.2% and after this level, a significant decline was recorded during both the years. As regards to the concentration of Ni is concerned, it increased significantly both in grain and straw with increasing levels of Ni spray and the maximum concentration was at T12 -Ni1.0%, during both the years. The uptake of Fe, Mn, Cu and Zn in grain of barley increased significantly during both the years up to T4 -Ni0.2%, thereafter, it declined significantly with successive increase in dose of Ni spray. Thus 0.2% foliar spray of NiSO4.7H2 O significantly increased growth, yield and Fe, Cu, Mn, Zn (micronutrients) status in barley.